Physical and mechanical properties of lamellar compounds of graphite - Костиков, Александр Анатольевич; Довгаль, Анна Николаевна; Кузнецов, Андрей Андреевич; Черномаз, Владимир Николаевич (Eastern-European Journal of Enterprise Technologies, 2013)
In this paper physical, mechanical and thermophysical properties of lamellar graphite compounds with various intercalants have been studied as a function of temperature and oxidants. The focus of the study was the influence of various factors on lamellar graphite compounds parameters, namely: elongation of samples, thermal expansion coefficient, thermal conductivity. The following factors have been considered: oxidant concentration in the synthesis of lamellar graphite compounds, the particle size of graphite, temperature of thermal expansion, nature of the intercalant. It has been shown that in foundry, namely in the heat insulation of casting heads and destruction of molding sand the acceptor graphite compounds are the most perspective (namely, bisulphate graphite and ammoniate). While preparation of mold core for metal casting with a large shrinkage lamellar graphite compounds with halides are the most prospective. The applying of lamellar graphite compounds in the foundry decreases metal consumption, improves core knockout tand quality of metal with a large shrinkage.